Reevaluating Joint Criminal Enterprise: Legitimacy and Reform in the Wake of R v Jogee - Wang, Suyi (Technium Social Sciences Journal, 2024)
This article examines the legitimacy and rationale of the Joint Criminal Enterprise (JCE) principle in international criminal law, focusing on the implications of the UK Supreme Court's decision in R v Jogee, which fundamentally abolished JCE as a legal principle. JCE, characterized by its complexity and contentious nature, has been criticized for being driven more by policy considerations than legal precedents. The article first explicates the concept and evolution of JCE, including common purpose liability and parasitic accessorial liability, and highlights the irrationalities within these principles. Through an in-depth analysis of the R v Jogee decision, the author argues that the ruling successfully rectified residual errors in criminal law, deeming the abolition of JCE consistent with legal logic and tradition. The article concludes with recommendations for enhancing transparency and clarity in prosecution and sentencing processes to restore public confidence in the criminal justice system. It also underscores the disproportionate negative impact of JCE on minority groups and young offenders, advocating for reforms to mitigate these effects.